The transition from socialism: State and civil society in Gobarchev's USSR - KUKATHAS, Chandran (Institutional Knowledge at Singapore Management University, 1991)
Considers the changes taking place in the USSR and the processes involved in the breakdown of socialism, particularly the prospects for the achievement of human liberties. The text is organized around the assumption that the distinction between "state" and "civil society" is a key analytical tool.